Parallel framework for dynamic domain decomposition of data assimilation problems: a case study on Kalman Filter algorithm. Issue 6 (8th February 2021) - D'Amore, Luisa; Cacciapuoti, Rosalba
Abstract: We focus on Partial Differential Equation (PDE)‐based Data Assimilation problems (DA) solved by means of variational approaches and Kalman filter algorithm. Recently, we presented a Domain Decomposition framework (we call it DD‐DA, for short) performing a decomposition of the whole physical domain along space and time directions, and joining the idea of Schwarz's methods and parallel in time approaches. For effective parallelization of DD‐DA algorithms, the computational load assigned to subdomains must be equally distributed. Usually computational cost is proportional to the amount of data entities assigned to partitions. Good quality partitioning also requires the volume of communication during calculation to be kept at its minimum. In order to deal with DD‐DA problems where the observations are nonuniformly distributed and general sparse, in the present work we employ a parallel load balancing algorithm based on adaptive and dynamic defining of boundaries of DD—which is aimed to balance workload according to data location. We call it DyDD. As the numerical model underlying DA problems arising from the so‐called discretize‐then‐optimize approach is the constrained least square model (CLS), we will use CLS as a reference state estimation problem and we validate DyDD on different scenarios.